Beware of Predatory Publishers! How Academic Libraries Can Safeguard Researchers Against Counterfeit Journals - Harrison, Jaydan (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2025)
Predatory publishers, also known as deceptive journals or pseudo-journals, are a growing problem in scholarly communications. These counterfeit periodicals exploit the principles of open access publishing for profit and can even engage in criminal practices. Early-career professionals and scholars from developing countries are particularly vulnerable to these tactics. Consequently, pseudo-journals pose a threat to the integrity of academic research. It is imperative for scholars to be cautioned and supported by knowledgeable allies, yet there is a lack of leadership and investment in this area. While some studies have acknowledged the usefulness of librarians as advocates and guides, few have investigated the specific role of academic libraries as warriors against predatory publishers. While most libraries currently have initiatives to inform researchers about predatory publishers, the general attitude indicates that more needs to be done. Therefore, a list of feasible, sustainable recommendations was compiled. This list aims to supply library workers with possible solutions to implement in their workplaces. Academic libraries have the potential to spearhead a movement that safeguards researchers against predatory publishers, thereby upholding publication ethics and the integrity of research.